Atividades musicais e corporais entre jovens e adolescentes na escola pública: pertencimento, subjetivação e cultura - Lavacca, Antonio Belforte (Universidade Federal de São Carlos, 2018)
From the development of activity workshops that encompassed the universes of music and body language, some students of a public school in the periphery of a medium-sized city have set out a few main axes: on the field of belonging, subjectivation and culture, we sought to dialogue with some artistic practices carried out collectively, with the goal of analyzing the possible contributions of the practices in the daily lives of the participants. The age range of adolescents and young people goes from 8 to 18 years old. It is a qualitative research that had a hybrid methodological procedure: the usage of field diaries, the usage of questionnaires to assist the characterization of the participants, interviews with teachers, school management, a mother and materiality of criticisms and artistic products made by adolescents and young participants that symbolized in practical results part of the actions in the field. The activity workshops are justified as part of the methodology. The results analyzed constitutive elements and workshops of activities and demonstrated that changes occurred along the students' daily lives when it comes to the collective meaning, affection and the construction of self through experience, the humanized relations and dialogue. From the point of view of employees, managers and parents, such as musical and corporal expression practices, such as workshops for contributory activities other than meetings, in other disciplines, in the community and at school, the socialization skills are generally unknown, of logical and behavioral reasoning, for example. The final considerations punctuated which were used in the practices of collective musical practices in the life of the participants. It has been observed that there has been an improvement in the relationship among themselves and colleagues, family, and they have shown a greater interest in sharing experiences and affections. The space where the workshops took place turned into a space of caring and collective belonging: a place where adolescents and young people could live and demonstrate their particularities, welcomed among all members.

A partir del desarrollo de talleres de actividades, que englobaban los universos de la música y de la expresión corporal, para algunos estudiantes de una escuela pública de la periferia de una ciudad mediana, fueron listados algunos ejes principales: acerca del campo de pertenencia, de la subjetivación y de la cultura, se buscó dialogar con algunas prácticas artísticas realizadas colectivamente, con el objetivo de analizar las posibles contribuciones de las prácticas en las vidas cotidianas de los participantes. La edad media de esos adolescentes y jóvenes se efectiva entre los 8 y 18 años. Se trata de una investigación cualitativa que contó con un hibridismo de procedimientos metodológicos: uso de diarios de campo, uso de cuestionario para auxiliar en la caracterización de los participantes, entrevistas con docentes, dirección escolar, una madre y la materialidad de creaciones y de productos artísticos realizados por los jóvenes participantes que simbolizaron en resultados prácticos parte de las acciones en campo. Los propios talleres de actividades a la vez se justificaron como parte de esta metodología. Los resultados analizaron elementos constitutivos de esos talleres de actividades y demostraron que ocurrió cambios en el cotidiano de los alumnos con relación a la pertenencia del colectivo, en el afecto y en la construcción de sí a través de la experiencia de las relaciones humanizadas y del diálogo. Bajo la óptica de los funcionarios, gestores y padres, las prácticas musicales y de la expresión corporal, los talleres de actividades contribuyeron para allá de los encuentros, en otras disciplinas, en la comunidad y en la escuela, de manera general, en lo que se refiere a las habilidades de socialización de raciocinio lógico y comportamentales, por ejemplo. Las consideraciones finales demarcaron cuáles fueron los efectos de las prácticas musicales en la vida de los participantes. Se observó que hubo una mejora en la relación con ellos mismos y con los compañeros, con la familia, además de la demostración de interés por compartir experiencias y afectos. El espacio donde ocurrieron los talleres de las actividades se convirtió en un espacio de pertenencia y cuidado colectivo: donde los adolescentes y jóvenes pudieron existir y demostrar sus particularidades, acogidas entre todos los involucrados.
Body and music activities amongst teens in public schools:belonging, subjetivation and culture
Keywords: Terapia ocupacional; Juventude; Coletividade; Práticas musicais; Socialização; Occupational therapy; Youth; Collectivity; Musical practices; Socialization; Juventud; Colectividad; Prácticas musicales; Socialización; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL